A QUANTITATIVE LITERATURE REVIEW ON THE IMPACT OF FINANCIAL RATIOS ON STOCK RETURN VOLATILITY IN GLOBAL CAPITAL MARKETS - Linatul Uyun (CV. Fahr Publishing, 2025)
This study conducts a quantitative literature review to investigate the impact of financial ratios on stock return volatility across global capital markets. While previous research often focuses on the relationship between financial ratios and average returns, this review shifts attention to volatility—an essential but less explored dimension of financial risk. Using a systematic search strategy, 53 peer-reviewed empirical studies published between 2015 and 2024 were selected from major databases such as Scopus, Web of Science, and ScienceDirect. The analysis identifies Return on Equity (ROE) and Debt-to-Equity Ratio (DER) as the most consistently significant predictors of return volatility, with ROE generally linked to lower volatility and DER to higher volatility. Additionally, Earnings per Share (EPS) and liquidity ratios demonstrate mixed and context-specific results. The review also evaluates methodological differences, showing that advanced models like GARCH and panel regressions yield more reliable volatility estimates than traditional OLS methods. A notable novelty of this research lies in its comparative and semi-quantitative approach, which synthesizes findings by region, ratio type, and method. Moreover, the inclusion of post-pandemic literature allows the study to reflect recent shifts in financial market behavior and risk interpretation. The results offer valuable insights for global investors, financial analysts, and policymakers aiming to understand how firm-level financial indicators influence market risk. In conclusion, this review not only maps empirical patterns but also highlights the importance of methodological precision and cross-market perspective in financial volatility research.